The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000486768
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Protects the Brain from Damage Induced by Epileptic Seizure via Nrf2/ARE Signaling

Abstract: Background/Aims: Ginsenoside Rb1 (Rb1) has been reported to have varieties of neuroprotective effects. This study aimed to evaluate the effects of Rb1 on pentylenetetrazol (PTZ)-induced rat brain injury and Mg2+ free-induced neuron injury and analyzed the detailed molecular mechanisms in vivo and in vitro. Methods: Seizure duration and latency were measured in epilepsy kindled rat. The cognitive impairment was assessed by Morris water maze (MWM) test. Oxidative stress parameters, malondialdehyde (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 59 publications
0
24
1
Order By: Relevance
“…Activation of the PI3K/Akt signaling pathway can alter neuronal apoptosis and attenuates the severity of seizures in experimental epilepsy-induced rats [20][21][22]. On the other hand, activation of the antioxidant Nrf2/ ARE pathway confers neuroprotective effects against pentylenetetrazole-or pilocarpine-induced brain damage in vivo and Mg 2+ free-induced seizure-like neuron injury [10,15,16,19]. In this study, the suppressed activity of the PI3K/Akt pathway and activated Nrf2/HO-1 pathway were observed, as indicated by decreased PI3K expression and Akt phosphorylation, as well as increased Nrf-2 nuclear translocation and HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the PI3K/Akt signaling pathway can alter neuronal apoptosis and attenuates the severity of seizures in experimental epilepsy-induced rats [20][21][22]. On the other hand, activation of the antioxidant Nrf2/ ARE pathway confers neuroprotective effects against pentylenetetrazole-or pilocarpine-induced brain damage in vivo and Mg 2+ free-induced seizure-like neuron injury [10,15,16,19]. In this study, the suppressed activity of the PI3K/Akt pathway and activated Nrf2/HO-1 pathway were observed, as indicated by decreased PI3K expression and Akt phosphorylation, as well as increased Nrf-2 nuclear translocation and HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, significant levels of free radicals and oxidative damage have been observed in the brain during seizures [11,12]. As one of the most important antioxidant pathways [13,14], the nuclear factor erythroid 2-related factor (Nrf2)/heme oxygenase-1 (HO-1) (Nrf2/HO-1) pathway has been recently shown to exert a significantly neuroprotective role in epilepsy [15,16]. Under normal conditions, Nrf2 is located in the cytoplasm as an inactive complex bound to the repressor protein named as Kelch-like ECH-associated protein 1 (Keap1); Under oxidative/electrophilic stress, Nrf2 dissociates from Keap1, then translocates to the nucleus where it binds to the antioxidant response element (ARE) to regulate the transcription of numerous antioxidant and cytoprotective genes, such as HO-1 and superoxide dismutase 1 (SOD1) [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Recent findings based on animal models studies have shown the neuroprotective effects of many compounds, such as the triterpene Ginsenoside Rb1 [95] and the alkaloid Glaucocalyxin B [96] as well as endogenous metabolites like alpha-lipoic acid [97] and estradiol [98], all involved in the activation of the Nrf2/ARE signaling. Aging is the main risk factor for neurodegeneration and is associated with enhanced ROS/RNS levels and lower antioxidant capacity.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Several studies have shown that gRb1 can protect neurons through activation of the Nrf2/ARE pathway in human SK-N-SH dopaminergic cells, SH-SY5Y cells, and neural progenitor cells [38][39][40]. Shi et al indicated that gRb1 protected the brain from neural injury through Nrf2 activation, and that the knockdown of Nrf2 counteracted the neuroprotective effect of gRb1 [41]. Liu et al indicated that gRb1 protected the spinal cord from oxidative stress by activating the Nrf2/ARE signal pathway [42].…”
Section: Effects Of Rg On Brain Ischemiamentioning
confidence: 99%